Herpes zoster on the forehead masquerading as an abscess complication to look out for: a case report - Ummer, Femina P.; Dhaiban, Tawfik M.; Veettil, Shajitha T. (International Journal of Research in Medical Sciences, 2019)
Herpes zoster or shingles is caused by the reactivation of latent varicella zoster virus (VZV) infection within the sensory ganglia. Primary VZV infection results in varicella (chickenpox) usually in childhood, characterized by vesicular lesions on the face, trunk, and extremities. Although herpes zoster can occur at any age, it is mainly a disease of adults over age 50 and/or immunocompromised individuals. Complications of herpes zoster include post herpetic neuralgia, herpes zoster ophthalmic us and less commonly acute retinal necrosis, aseptic meningitis, and encephalitis. Here we present the case of a 51-year-old female patient with Herpes Zoster infection involving the dermatome on the forehead, initially misdiagnosed, to alert clinicians to create awareness and minimize misdiagnosis of other patients with similar cases. It is unusual to find patients presenting with infection involving the dermatome of the forehead.